50+ years later, prosthetic valve endocarditis still confounds. Issue 1 (19th January 2023) - Block, Peter C.
Key Points: Prosthetic valve endocarditis is a rare but important complication of transcatheter aortic valve replacement. Treatment of prosthetic valve endocarditis in patients who are status‐post transcatheter aortic valve replacement is difficult due to antibiotic resistance, and outcomes indicate a mortality >10%. In the absence of clinical trials of effective prophylactic antibiotics at the time of transcatheter aortic valve replacement, a careful search for infection both pre‐ and post‐transcatheter aortic valve replacement is critical to prevent infection and treat infection early.